Perwalian Anak di Luar Nikah di Kabupaten Bone Bolango Perspektif Hukum Adat dan Hukum Islam - Anton Panto; Zulkarnain Suleman; Mustaqimah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2021)
This article aims to find out and analyze the opinion of traditional leaders on the guardianship of children out of wedlock, what are the opinions of traditional stakeholders in Bone Bolango who allow guardianship for children out of wedlock and the resolution of the issue of guardianship of children out of wedlock. This research is descriptive research intended to describe a situation or a certain population area that is factual in a systematic and accurate manner. To enrich and sharpen argumentation analysis. This research uses a phenomenological approach. Based on the results of the research that in guardianship for children out of wedlock the perspective of customary law in Bone Bolango is allowed for biological fathers to become guardians for their children if the biological father marries the child's mother before the child is born. This is because of the customary view of tinepo (wisdom). However, if the child was born before the consent of the parents, then the biological father cannot be the guardian for the child.